Suddenly a clown: reflections about gestures in a personal experience in Bogotá (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
This article is an experience report that starts from a personal experience lived in a clown workshop developed by the Colombian actress Viviana Bernal in 2022 in Bogotá. This work aimed, through the interdisciplinarity between theater, dance and clown studies, to analyze concrete examples that were taken from this workshop to reflect on some questions: How does a gesture produce laughter? What is the relationship between the perception of the gesture and the historical and social issues? After such reflections based on the theories developed by Merleau-Ponty, Jorge Dubatti, Hubert Godard and others, it was possible to verify the relevance of this study, which highlight the recording process and reflections of the actor's empirical experience on his body training and also of the audience about their perceptions/receptions as a tool for research in art and as a political positioning.
Keywords: Clown; Gesture; Dance; Theater; Experience